Предмет: Математика,
автор: danilishutin8
5 - 3 ( x - 2 ( x - 2 ( x -2) ) ) = 2
Ответы
Автор ответа:
0
5-3(х-2(х-2(х-2)))=2
5-3(х-2(х-2х+4))=2
5-3(х-2х+4х-8)=2
5-3х+6х-12х+24=2
29-9х=2
29-2=9х
27=9х
х=27/9
х=3
5-3(х-2(х-2х+4))=2
5-3(х-2х+4х-8)=2
5-3х+6х-12х+24=2
29-9х=2
29-2=9х
27=9х
х=27/9
х=3
Автор ответа:
0
5-3(х-2(х-2х+4))=2
5-3(х-2х+4х-8)=2
5-3х+6х-12х+24=2
-3х+6х-12х=2-24-5
-9х=-27
х=3
5-3(х-2х+4х-8)=2
5-3х+6х-12х+24=2
-3х+6х-12х=2-24-5
-9х=-27
х=3
Похожие вопросы
Предмет: Математика,
автор: senanisgenderov7
Предмет: Математика,
автор: superchelovek228
Предмет: Литература,
автор: muslimkobey498
Предмет: Химия,
автор: metro2012